Investigating chaos in the Nigerian Asset and Resource Management (ARM) discovery fund - Ibiyinka A. Fuwape; Samuel T. Ogunjo (CBN Journal of Applied Statistics, 2013)
This paper investigates chaos in a Nigerian mutual fund, Asset and Resource Management Company Limited (ARM) for a period of eleven years. The existence of chaotic signals in the data was identified by the reconstruction of the phase space of the daily closing price of the fund and the delay time was quantified using mutual information function and the embedding dimension by the false nearest neighbours, where the values were identified to be 15 and 20 respectively. The presence of chaotic signals in the ARM data was further confirmed by the correlation dimension method which yielded a dimension of 2.2 and by the Lyapunov exponent, in which the largest Lyapunov exponent is 0.0528. The predictability of the fund was evaluated from the inverse of the largest Lyapunov exponent as 19 days.
Keywords: G01; H12; P47; 330; discovery fund; chaos; time series; lyapunov exponent; correlation dimension; correlation integral